2005
DOI: 10.1093/jnci/dji060
|View full text |Cite
|
Sign up to set email alerts
|

Physician Predictors of Mammographic Accuracy

Abstract: Raising the annual volume requirements in the Mammography Quality Standards Act might improve the overall quality of screening mammography in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 29 publications
9
98
2
1
Order By: Relevance
“…Our study support findings from five studies showing volume to be of importance. [18][19][20][21][22] For example, Theberge et al 21 showed that radiologist who read more than 2,000 mammograms per year had higher sensitivity while maintaining low specificity. Our results are in contrast with those of previous studies finding that increased volume may not necessarily increase performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study support findings from five studies showing volume to be of importance. [18][19][20][21][22] For example, Theberge et al 21 showed that radiologist who read more than 2,000 mammograms per year had higher sensitivity while maintaining low specificity. Our results are in contrast with those of previous studies finding that increased volume may not necessarily increase performance.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologist training in general has been associated with increased performance. [12][13][14][15][16][17] Data on the relationship between volume read per radiologist and performance are, however, conflicting, 13,[18][19][20][21][22] whereas associations have been found between some other indicators of radiologists' experience and performance. [23][24][25] However, most studies focused on mammography screening, and no large community based study has evaluated the association between organisational factors and performance of diagnostic mammography.…”
mentioning
confidence: 99%
“…Barlow et al report that more recently qualified radiologists have higher sensitivity but lower specificity which might suggest that years of experience lead to a change in the threshold for recalling a patient rather than improved accuracy [24]. However Smith-Bindeman et al have found that radiologists with more years of qualification had better specificity and slightly improved or at least equal sensitivity, suggesting that the improved specificity is the result of more accurate interpretation [25]. Their analysis is summarised in Figure 1.…”
Section: Studies Of Medical Decision-makingmentioning
confidence: 99%
“…It might be that radiologists who view more cases per annum are not being given sufficient feedback on performance, or adequate opportunity for reflection for the experience to be beneficial. Smith-Bindeman et al report radiologists reading 2500-4000 mammograms a year had improved specificity but that this effect was not found in radiologists reading more than 4000 per annum [25]. We need to ensure that all radiologists, but particularly recently qualified radiologists, are given not just experience but also the opportunity to learn from it.…”
Section: Implications For Radiological Trainingmentioning
confidence: 99%
“…Screening accuracy could be enhanced by either improving image quality or by improving the accuracy of radiologists who interpret mammograms [1]. Differences in radiologists' training, experience and reading volume may affect their clinical recommendations and interpretations [2][3][4][5][6]. Regulations set forth by the Food and Drug Administration's (FDA) Mammography Quality Standards Act (MQSA) [7] require continuing medical education (CME) for all radiologists who interpret mammograms [8].…”
Section: Introductionmentioning
confidence: 99%